Determination of the compressed zone shape of concrete in reinforced concrete T-section beams under biaxial bending - Usenko, Yuliia; Pavlikov, Andriy (Academic journal Industrial Machine Building Civil Engineering, 2022)
The method of the calculation case determining for biaxial bent reinforced concrete T-shaped elements using a complete concrete deformation diagram is presented. Analytical dependences are presented in tabular form, according to which it is possible to determine the neutral line position case in the cross-section of the reinforced concrete element. The given analytical dependences use the concrete relative strains level in the most compressed fiber. It allows the determination of the change of the neutral line position from the beginning of loading till the destruction moment of the reinforced concrete beam element. This approach will allow to determine both the bearing capacity and the serviceability limit state of biaxial bent reinforced concrete T-section beams.